2019
DOI: 10.3390/fishes4010002
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Barrier Functions of Fish under Changing Environmental Conditions

Abstract: The skin, gills, and gut are the most extensively studied mucosal organs in fish. These mucosal structures provide the intimate interface between the internal and external milieus and serve as the indispensable first line of defense. They have highly diverse physiological functions. Their role in defense can be highlighted in three shared similarities: their microanatomical structures that serve as the physical barrier and hold the immune cells and the effector molecules; the mucus layer, also a physical barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 60 publications
1
63
0
1
Order By: Relevance
“…of acute hypercapnia exposure also on the external mucosal barrier. Mucosal surfaces (i.e., skin, gills and gut) provide fish the first line of defense, and skin mucus, similarly to peripheral blood, is armed with potent molecules, including lysozymes, complement proteins, lectins and antimicrobial peptides with important immune roles (Cabillon and Lazado, 2019). In this study, the modulation of humoral parameters found both in skin mucus and plasma seem to suggest some degree of adjustment to the acidic ambient water, even after a short period.…”
Section: Discussionmentioning
confidence: 59%
“…of acute hypercapnia exposure also on the external mucosal barrier. Mucosal surfaces (i.e., skin, gills and gut) provide fish the first line of defense, and skin mucus, similarly to peripheral blood, is armed with potent molecules, including lysozymes, complement proteins, lectins and antimicrobial peptides with important immune roles (Cabillon and Lazado, 2019). In this study, the modulation of humoral parameters found both in skin mucus and plasma seem to suggest some degree of adjustment to the acidic ambient water, even after a short period.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding fish immunity, several studies have demonstrated the relationship between photoperiod and the immune system [8,9,12,15,31]. For example, a study conducted by our group (also on gilthead seabream and European sea bass) reported how the photoperiod affected some seric immune parameters (natural hemolytic complement, lysozyme and peroxidase activities) [8].…”
Section: Discussionmentioning
confidence: 82%
“…In this sense, it has been demonstrated that some components of the fish immune system also exhibit daily variations [8,12], but, to the best of our knowledge, the available information on this topic is very limited because such information mostly focus on seasonal variations (reviewed by [2]). In the above studies, daily rhythmicity was demonstrated in several components of fish humoral (such as complement, lysozyme, and peroxidase activities and globulin level) and cellular (leucocyte phagocytosis and production of reactive oxygen species) immunity [12,15,16]. Our group evaluated the effects of photoperiod on some seric immune parameters of gilthead seabream (S. aurata L.) and European sea bass (D. labrax) specimens [8], which are the most widely farmed fish species in the world [14].…”
Section: Introductionmentioning
confidence: 98%
“…Fish have an intimate interaction with their immediate environment, where several challenges present themselves, including biological (e.g., parasites, bacteria, viruses), chemical (e.g., pollutants, therapeutics), and physical (e.g., handling sorting in commercial production). 1 These challenges put significant pressure on the adaptive and protective strategies of fish. The gills, skin, gut, and nasal mucosa are the major mucosal organs in fish, and they represent the interface between the internal and the external environments.…”
Section: Mucosal Barriers Of Fishmentioning
confidence: 99%